Christian Vikings: Norsemen in Western Europe in the 12th century - Jesch, Judith (Presses universitaires de Caen, 2014)
From the late 11th century onwards, northern Europeans were also infected with the crusading spirit that swept the whole of Europe. With their knowledge of the East, their military abilities and experience, and their relatively new enthusiasm for Christianity, upper-class Scandinavians were well-placed to lead their own warlike expeditions to the Holy Land. Such upper-class Scandinavians were also both patrons and practitioners of poetry, and this paper examines two 12th-century expeditions led by Scandinavian rulers, King Sigurðr of Norway and Earl Rögnvaldr of Orkney, through the poetry they occasioned. In the 12th century, Norse culture derives its value and its new energy from this process of interaction with other cultures. An important aspect of this new historical context was the crusading impulse, involving as it did travel to distant places and encounters with other cultures. The poetry reveals that the Vikings began to experience the world of Western Europe in a new way, no longer simply as destinations for raiding and trading, but as destinations for spiritual and cultural activities. These encounters are faithfully recorded in their poetry, which achieved the unusual feat of continuing its tradition modes while also being highly receptive to new concepts.